A9.06 Analysis of cell-specific interferon response in systemic lupus erythematosus using a novel flow cytometric assay. (24th February 2016) - El-Sherbiny, YM; Yusof, MY Md; Hensor, EM; Psarras, A; Mohamed, A; Wittmann, M; Emery, P; Vital, EM
Abstract : Background and objectives: Type I interferons (IFN-I) have diverse effects on immune cell populations in SLE, Measuring IFN-I using whole blood interferon-stimulated gene (ISG) expression does not completely explain clinical features of SLE. Objective: develop a cell-specific assay using a surface protein encoded by an ISG ( BST2 ). This would allow convenient analysis of IFN response in individual populations to improve immunophenotyping of SLE patients. Materials and methods: PBMCs from 133 SLE patientsand 19 healthy controls (HC) were analysed by flow cytometry for cell surface BST2 protein on each immune cell subset. Cells were FACS-sorted into naïve and memory B-cells, plasmablasts, CD3 + T-cells, NK-cells and monocytes in 12 SLE patients and 16 healthy controls. Expression of BST2, as well as 32 other ISGs, were measured using qPCR. Results: Analysis of sorted cells confirmed that surface BST2 is a valid cell-specific IFN assay. BST2 expression correlated with BST2 surface protein within each immune subset: naïve B-cells (r = 0.63, p = 0.009); memory B-cells (r = 0.78, p < 0.001); plasmablasts (r = 0.58, p = 0.018);NK cells (0.63, p = 0.008);T-cells (r = 0.61, p = 0.012); monocytes (r = 0.47, p = 0.064). We next used surface BST2 to compare IFN activity of each subset with clinical features in 133 patients. A significant correlation between the PBMC 33-gene IFN score and surface BST2 for each cell subset (all p < 0.001) confirmed validity of BST2 biomarker in this larger population as a measure of overall IFN status. BST2 was significantly higher in SLE than HC on naïve and memory B-cells (p = 0.004, p = 0.003), plasmablasts (p = 0.047), T cells (p = 0.043), but not different on monocytes (p = 0.406). Association of disease activity (total BILAG) with BST2 on naïve and memory B-cells (Tau-a = 0.23 and 0.22 respectively) was substantive and approximately twice as strong as monocytes and T-cells (Tau-a = 0.12 and 0.14). A similar pattern was seen for anti-dsDNA titre, with no association with monocyte BST-2 (Tau-a = 0.07) but a substantive association for memory B cell BST-2 (Tau-a = 0.18). Conclusion: IFN-I response differs in cell subsets. This can be measured in a fast, cost-effective, convenient assay using flow cytometric analysis of surface BST2. Our results show that IFN activity measured on B cells is more clinically relevant than on other cell populations.